Effectiveness of various cast covers in the pediatric population - Amit Parekh, MD; John Moon, MD; David Roberts, MD; Verena M. Schreiber, MD (Elsevier, 2024)
ABSTRACT: Background: Keeping casts dry is a challenge in pediatric Orthopaedics. A wet cast risks skin complications and generally requires a cast change resulting in unplanned visits and increased health care costs in patients undergoing cast immobilization. Previous research on the effectiveness of cast covers has only reviewed adult models. We evaluated the efficacy of different commercially available cast covers and do-it-yourself (DIY) methods for keeping casts dry in different-sized pediatric arm models and compared the relative costs of using each method. Methods: Short arm casts were applied to plastic mannequin arms representing pediatric patients ages 3, 6, and 12 years old. Different cast covers or DIY methods were applied over each cast and the limbs were then submerged in water for 1 minute. Water absorption was calculated by comparing the mass before and after submersion as measured with a digital scale. Each test group had 6 trials as determined by a power analysis. Statistical analysis was done using a nonparametric test with additional post-hoc analysis. Cost-effectiveness was estimated for typical materials needed for use over a 6-week period. Results: A plastic bag and duct tape were the most effective in keeping a cast dry. Other DIY methods (plastic bag and rubber bands, adhesive film) were not effective. There were several highly effective commercial cast covers across age groups, including Bloccs, Seal-Tight, and DryPro. Other commercial cast covers tested had inferior performance. Of the effective methods, a single plastic bag and duct tape were the most cost-effective. Discussion/Conclusions: A plastic bag and duct tape was overall the most clinically and cost-effective method of avoiding a wet cast, with good to excellent results across arm size/age groups. Findings from this study may better inform patients about ways to keep casts dry, avoid unnecessary visits for cast changes, and decrease associated costs and risk of complications. Key Concepts: (1) A plastic bag and duct tape were the most effective methods for keeping a cast dry across various arm sizes seen in pediatric Orthopaedics. (2) Other DIY methods (plastic bags and rubber bands, adhesive film) were ineffective, and should not be recommended. (3) Performance of commercial cast covers was variable. Several commercial cast covers (Bloccs, Seal-Tight, DryPro) were effective, but others (Walgreens, Curad) were not. (4) Amongst effective methods, a plastic bag and duct tape were also the least expensive.Level of Evidence: II, prospective comparative study.